Uso tradicional de plantas medicinales en gestantes y puérperas de las comunidades nativas y mestizas del cantón Yantzaza - Abad Troya, Esther Isolina (2024)
Traditional medicinal plants are a fundamental part of understanding the ancestral traditions of pregnant and postpartum women in native and mestizo communities of Yantzaza canton. This study aimed to identify the community that primarily uses medicinal plants for therapeutic purposes in Yantzaza canton. It identified the most commonly used medicinal plants, described their use during each stage of pregnancy and postpartum, and characterized the most common preparation methods employed by pregnant and postpartum women from native and mestizo communities in Yantzaza canton, Zamora Chinchipe province. The research adopted a mixedmethods approach, combining quantitative and qualitative perspectives, with a cross-sectional design that included 60 women who agreed to participate after providing informed consent and completing a survey on the traditional use of medicinal plants. Ten participants were excluded for not meeting the inclusion criteria, which specified that women must be between 18 and 45 years old, permanent residents of Yantzaza canton, belong to the mestizo or native population, be in pregnancy or postpartum, and have used medicinal plants for therapeutic purposes. At the end of the research work, it could be observed that the ethnic group that uses medicinal plants most frequently corresponds to the group of mestizo women (87.50%). Concerning the use of medicinal plants, it was found that the most frequently used plant was chamomile (23.4%), with the greatest use during the first trimester (34.27%) and the most common form of preparation was infusions (78.5%)